2007
DOI: 10.1038/sj.bjc.6603781
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer prodrugs of butyric acid and formaldehyde protect against doxorubicin-induced cardiotoxicity

Abstract: Formaldehyde has been previously shown to play a dominant role in promoting synergy between doxorubicin (Dox) and formaldehyde-releasing butyric acid (BA) prodrugs in killing cancer cells. In this work, we report that these prodrugs also protect neonatal rat cardiomyocytes and adult mice against toxicity elicited by Dox. In cardiomyocytes treated with Dox, the formaldehyde releasing prodrugs butyroyloxymethyl diethylphosphate (AN-7) and butyroyloxymethyl butyrate (AN-1), but not the corresponding acetaldehyde-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…The chemotherapeutic agent doxorubicin alone caused the mice to lose weight following exposure, as shown previously (11)(12)(13)32). Whole body fat and lean mass were significantly decreased, a phenomenon that occurs in the clinic.…”
Section: E298 Cancer Chemotherapy and Mitochondrial Dysfunctionmentioning
confidence: 57%
“…The chemotherapeutic agent doxorubicin alone caused the mice to lose weight following exposure, as shown previously (11)(12)(13)32). Whole body fat and lean mass were significantly decreased, a phenomenon that occurs in the clinic.…”
Section: E298 Cancer Chemotherapy and Mitochondrial Dysfunctionmentioning
confidence: 57%
“…Since we have shown that AN-7 protected cardiomyocytes against Dox toxicity [10], in this study we address the question of whether the combinations of AN-7 and Dox as well as AN-7 and anti-HER2, will display reduced toxicity in normal cells as well as increased anticancer activity against cancer cells. Moreover, we aimed to characterize some of the specific biological changes associated with the response to the treatments in the different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…At doses of 25-50 mg/kg, it inhibited tumor growth, angiogenesis and metastasis in various mouse cancer models [6][7][8]. Importantly, while AN-7 interacted synergistically with doxorubicin (Dox) in killing cancer cells, as was demonstrated by Median Effect Analysis (MEA) [9], it also protected neonatal rat cardiomyocytes and adult mice against Dox toxicity [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…The formaldehyde-releasing prodrugs induce cell death in a variety of cancer cell lines while exhibiting significantly lower toxicity toward human cells including mononuclear, astrocytes and cardiomyocytes [5,6,13]. The observation that AN-7 displays contrasting biological roles toward cancer versus normal myocardial cells, demonstrates a diversity of activity and specificity tailored to particular cell types that is most desirable for an antineoplastic agent.…”
Section: Introductionmentioning
confidence: 93%
“…We have described the synergistic interaction between AN-7 or AN-9 and Doxorubicin (Dox) [5,8], and the protection provided by the AN-7 against the cardiotoxicity of Dox, where the formaldehyde released intracellularly from the prodrug was shown to be a dominant factor in the cardioprotective activity and in killing cancer cells [13]. The formaldehyde-releasing prodrugs induce cell death in a variety of cancer cell lines while exhibiting significantly lower toxicity toward human cells including mononuclear, astrocytes and cardiomyocytes [5,6,13].…”
Section: Introductionmentioning
confidence: 99%